1999
DOI: 10.1021/bi990114r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Adenophostin, a Very Potent Ca2+ Inducer, at the d-myo-Inositol 1,4,5-Trisphosphate Receptor

Abstract: The recognition mode of adenophostin A at the D-myo-inositol 1,4, 5-trisphosphate [Ins(1,4,5)P(3)] receptor was investigated. Comparison of conformations of Ins(1,4,5)P(3) and adenophostin A by using the combination of NMR and molecular mechanics (MM) calculations demonstrated that adenophostin A adopted a moderately extended conformation regarding the distance between the 2'-phosphoryl group and the 3' ',4' '-bisphosphate motif, as suggested previously [Wilcox, R. A. et al. (1995) Mol. Pharmacol. 47, 1204-121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Inositol 1,4,5‐trisphosphate and AdA are each full agonists of the IP 3 R (Rossi et al ., 2009). Both IP 3 and AdA bind to the IBC, and despite their structural differences, the 3",4"‐bisphosphate and 2"‐hydroxyl groups of AdA evidently mimic the essential 4,5‐bisphosphate and 6‐hydroxyl of IP 3 (Figure 1B) (Takahashi et al ., 1994c; Hotoda et al ., 1999; Correa et al ., 2001; Rosenberg et al ., 2003). These features probably account for the binding of AdA to the IBC (Rosenberg et al ., 2003), but they do not explain the ability of AdA to bind to IP 3 R with greater affinity than IP 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Inositol 1,4,5‐trisphosphate and AdA are each full agonists of the IP 3 R (Rossi et al ., 2009). Both IP 3 and AdA bind to the IBC, and despite their structural differences, the 3",4"‐bisphosphate and 2"‐hydroxyl groups of AdA evidently mimic the essential 4,5‐bisphosphate and 6‐hydroxyl of IP 3 (Figure 1B) (Takahashi et al ., 1994c; Hotoda et al ., 1999; Correa et al ., 2001; Rosenberg et al ., 2003). These features probably account for the binding of AdA to the IBC (Rosenberg et al ., 2003), but they do not explain the ability of AdA to bind to IP 3 R with greater affinity than IP 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It binds to a site that substantially overlaps the IP 3 -binding site, 6 and structure–activity studies with synthetic analogues of AdA have established that the adenine (or another aromatic group) is essential for its enhanced affinity. 6,7 …”
mentioning
confidence: 99%
“…It has been suggested that the 2′-phosphate of AdA interacts with the IBC in a manner that allows it to behave as a super-optimal mimic of the 1-phosphate of IP 3 [44], [45]. However, our recent study combining structure-activity analyses with mutagenesis of the binding site suggest that the 1-phosphate of IP 3 is more important for binding than is the 2′-phosphate of AdA [12].…”
Section: Resultsmentioning
confidence: 85%